Short Communication: Diversity and abundance of soil insects at Jeruk Manis Protected Forest in East Lombok (Indonesia) using several trapping methods - IMMY SUCI ROHYANI; HILMAN AHYADI (Biodiversitas Journal of Biological Diversity, 2017)
Rohyani IS, Ahyadi H. 2017. Short Communication: Diversity and abundance of soil insects at Jeruk Manis Protected Forest in East Lombok (Indonesia) using several trapping methods. Biodiversitas 18: 809-812. Insects are the most successful organisms because it can live in almost all types of habitats, namely water (freshwater and sea), land, air, and even in both hot and cold climates. Identification of soil insects in a certain type of habitat requires practical, easy, inexpensive, and efficient collection methods so as to obtain high abundance and diversity of soil insects. This study aims to analyze the diversity and abundance of soil insects using several trapping methods in Jeruk Manis Protected Forest in East Lombok. There are five trapping methods applied in this study; (i) pitfall trap, (ii) pitfall traps with bait, (iii) yellow pan traps, (iv) soil sampling, and (v) forest floor collection. The findings show that the overall diversity of soil insects in Jeruk Manis Protected Forest is moderate (1.44), while its evenness level is low (0.48). Soil sampling method provides diversity value of 2.36 and evenness level of 0.89, which is also the highest one among the other methods. Pitfall traps with bait give high individual number of soil insects (10.577 individuals). The highest number of soil insect orders is obtained through forest floor collection with 11 orders, while the highest number of soil insect families is obtained through pitfall trap with 30 families. The taxa of soil insects with relatively highest abundance consecutively are Hymenoptera (Formicidae), Collembola (Isotomidae, Entomobryidae), Coleoptera (Hydrophilidae, Ptiliidae, Scarabeidae), and Diptera (Drosophilidae).